Comparison of cultural characteristics and genomic profiles of two strains of bluetongue virus 1 of Indian origin - MALIK, YASHPAL; MINAKSHI, MINAKSHI; MAAN, SUSHILA; PRASAD, G (The Indian Journal of Animal Sciences, 2013)
Replication kinetics of 2 genomically different strains (BLUV-H and BLUV-A) of bluetogue virus serotype 1 (BLUV 1) was studied in BHK 21 cell culture by sequential harvesting of the infected cells. In addition, cytopathic effects (CPE) in the infected cells were also observed on differnet intervals post infection (PI). Analysis of comparative profiles of these 2 strains in respect of cytopathic changes and electrophoretic migration pattern of genomic RNA segments provided significant differences between these strains. BLUV-A was more cytopathogenic compared to BLUV-H in BHK 21 cells. RNA-polycrylamide gel electrophoresis indicated presence of extra segments in BLUV-H. Though there was not much difference in the cell culture titres of these 2 strains at different intervals PI, variation in the nature of cytopathic effects was noticeable. Electrophoretic analysis of the viral genome revealed that extra bands in BLUV-H started appearing only after 12 hrÂ PI. This study also provided idea about the peak time for harvesting of the virus as maximum titre of the virus was observed at 28 hrÂ PI which started declining 32 hr PI if kept in incubator at 37oC, The study suggsted that the 2 strains were not only different in genomic profile but also differed in their cytopathogenicity in BHK 21 cell culture. Genomically different strains of the same serotype might account for the differences in cytopathogenicity or clinical disease in susceptible species. Futher studies are warranted to characterize these strains in terms of their genomic sequence variation, virulence and immunogenic attributes which could help in development of a suitable vaccine based on the local strains.